Appropriation of Adult Education for Academic Achievement Towards Sustaining the Rights of Physically Challenged Students in Higher Institutions in Lagos - Ajayi, Rachael Adejoke; Aranmolate, Temitope Raheedat (Journal of Education and Practice, 2023)
Purpose: The study examined the appropriation of adult education for academic achievement towards sustaining the rights of physical challenged students in higher institutions in Lagos. Methodology: The research design employed in the study was a descriptive survey. The population consisted of all higher institutions located in Lagos State. To gather data, a simple random sampling technique was utilized to choose ten (10) higher institutions from which fifteen (15) physically challenged students were selected from each institution. This amounted to a sample size of one hundred and fifty (150) respondents for the study. The data collection process utilized a self-developed questionnaire as the primary instrument. It was developed in 2 Likert scale of Agreed and Disagreed. The instrument was moderated by experts who affirmed its validity. The reliability of the instrument was assessed through the utilization of the Pearson Product Moment Correlation Coefficient (PPMC). The data collected were then analyzed using statistical tools such as simple percentage and standard deviation. Findings: The study's findings indicated that adult literacy significantly contributes to adult sustainable development, fostering economic, social, and environmental sustainability. Furthermore, it establishes conducive circumstances for empowering active global citizens. By effectively employing adult education, individuals with physical challenges can acquire a comprehensive comprehension of various concepts and lead their lives in a proficient manner. Unique Contributions to Theory, Policy and Practice: Adult education has a wide-ranging positive influence on various aspects relevant to adults. Importantly, these advantages extend beyond the professional sphere and encompass different aspects of daily life for individuals with physical challenges. These benefits extend beyond the professional realm and extend to various facets of everyday life for physically challenged individuals. As a result, it is recommended that to guarantee the sustainability of the human rights of physically challenged students, the government should assume the primary responsibility of providing trained and qualified teachers/facilitators, along with other supportive staff, who will cater to the educational needs of these special students.